Formation of Hydroxyl-Amide Solid Dispersion Involving Azithromycin and Chitosan-Alginate Biopolymer to Increase the Dissolution Rate of Azithromycin - Mardiyanto; Budi Untari; Ady Mara; Diko Fahri Ferdiansyah (Science and Technology Indonesia, 2023)
Research to increase the solubility of active pharmaceutical ingredients is usually conducted by reducing the particle size. This research is one side that used the solid dispersion systems to increase solubility, especially on macrolide antibiotics for which there is still little information. The co-grinding technique on azithromycin-chitosan-alginate was chosen to produce a solid dispersion system. The parameters observed were changes in crystal structure, FTIR spectral patterns, morphological changes, and dissolution profile changes. The results of this research showed a change in the pattern of X-diffraction of azithromycin, physical interaction between azithromycin and the polymer, changes in the image of surface of solid dispersions, the solubility of solid dispersions in simulated-intestinal-fluid (SIF) solutions, and an increase in the dissolution rate of azithromycin indicating that the co-grinding technique to produce solid dispersions can increase the solubility of azithromycin.